Analysis of hard palate topography in the Polish population, with special emphasis on the greater palatine canal and foramen - Tomaszewska, Iwona (2014)
Aim: (1) to localize the GPF in relation to multiple anatomical landmarks; (2) to assess the length and shape of the greater palatine canal (GPC); (3) to create a mathematical model which would differentiate between males and females using hard palate measurements.Materials and Methods: 150 dry, adult, human skulls and 1200 head CT scans were measured in terms of hard palate topography, GPF relation to anatomical reference points, and the length and pattern of the GPC. A systematic literature review and a meta-analysis on the subject of GPF relation to the maxillary molars were conducted.Results: The studied group comprised 1350 samples (695 female – 51.5%), mean age 44.9±17.1 years. On average the GPF was positioned 15.9±1.5mm from the midline maxillary suture (MMS). All performed measurements were significantly (p<0.0001) larger in males than in females. The equation based on the depth of the right GPC, the O-SNP distance and the anterior width of the palatal arch (AWPA) had a reliability rate of 78.37%. The pooled prevalence of the GPF being positioned opposite the M3 was 63.9% (95%CI=56.6-70.9%).Conclusions: The GPF is most often located opposite the M3 in the majority of the world’s populations. The maxillary molars are the best landmarks for locating the GPF. The most prominent sexually dimorphic parameters are the O-SNP, the GPC depth and the AWPA.
Keywords: molar teeth; hard palate; greater palatine foramen; greater palatine canal; anatomical variability